Prevalence of ADHD and Methylphenidate Usage - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
An analysis of data obtained from the National Ambulatory Medical Care Survey (NAMCS), 1990-1995, for children aged 5 through 18 years, was performed at Washington State University, to discern trends in the prevalence of US office-based visits for ADHD and for prescriptions of stimulant medications, including methylphenidate (MPH), for ADHD treatment.